The free-radical scavenger edaravone accelerates thrombolysis with alteplase in an experimental thrombosis model. Issue 6 (June 2015) - Yamashita, Tsutomu; Sato, Takumi; Sakamoto, Kumi; Ishii, Hiromitsu; Yamamoto, Junichiro
Abstract: Background and Purpose: Reperfusion injury after thrombolytic therapy can have adverse neurologic effects. The free-radical scavenger edaravone is used in combination with the recombinant tissue plasminogen activator alteplase to treat acute ischemic stroke. However, basic investigations of this combination use remain inadequate. Here, we used an in vivo model to investigate the effects of edaravone on alteplase-induced thrombolysis. Methods: Thrombolysis was evaluated by using a He-Ne-laser–induced thrombosis model in rat mesenteric microvessels. Changes in thrombus volume were analyzed with the image analysis software Image-Pro Plus (Media Cybernetics, USA). There were three experimental groups (placebo, alteplase 0.6 mg/kg, alteplase 0.6 mg/kg + edaravone 10.5 mg/kg). Sequential changes (0 to 60 min) in thrombus volume were compared by using a relative optical density method that we had used previously. Results: In the placebo group, the thrombus volume at 60 min, reflecting the extent of thrombolysis, was 97.2% ± 5.7% of the initial value. In the alteplase group, thrombus volume decreased to 70.7% ± 4.1% (P < 0.01) after 20 min and 14.2% ± 6.6% after 60 min. In the alteplase + edaravone group, thrombus volume decreased to 66.9% ± 7.2% (P < 0.001) after 10 min and 10.9% ± 2.3% after 60 min. Conclusions: These results support the hypothesis that edaravone accelerates thrombolysis by alteplase. Highlights: Thrombolysis by Alteplase showed dose dependence in thrombosis model. The combination of Edaravone and Alteplase accelerated thrombolysis by Alteplase. This combination will be clinically useful for thrombolytic therapy. The edaravone may prevent a new thrombus formation as one possibility by mediating the selectin downregulation. Edaravone may accelerate thrombolysis as one possibility by enhancement of NO release.